Simultaneous silencing of juvenile hormone metabolism genes through RNAi interrupts metamorphosis in the cotton boll weevil - Vasquez, Daniel D. N.; Pinheiro, Daniele H.; Teixeira, Lays A.; Moreira-Pinto, Clidia E.; Macedo, Leonardo L. P.; Salles-Filho, Alvaro L. O.; Silva, Maria C. M.; Lourenço-Tessutti, Isabela T.; Morgante, Carolina V.; Silva, Luciano P.; Grossi-de-Sa, Maria F. (Frontiers in Molecular Biosciences, 2023)
The cotton boll weevil (CBW) (Anthonomus grandis) is one of the major insect pests of cotton in Brazil. Currently, CBW control is mainly achieved by insecticide application, which is costly and insufficient to ensure effective crop protection. RNA interference (RNAi) has been used in gene function analysis and the development of insect control methods. However, some insect species respond poorly to RNAi, limiting the widespread application of this approach. Therefore, nanoparticles have been explored as an option to increase RNAi efficiency in recalcitrant insects. Herein, we evaluated the potential of chitosan-tripolyphosphate (CS-TPP) and polyethyleneimine (PEI) nanoparticles as a dsRNA carrier system to improve RNAi efficiency in CBW. Different formulations of the nanoparticles with dsRNAs targeting genes associated with juvenile hormone metabolism, including juvenile hormone diol kinase (JHDK), juvenile hormone epoxide hydrolase (JHEH) and methyl farnesoate hydrolase (MFE), were tested. The formulations were delivered to CBW larvae by injection (0.05 - 2 µg), and the expression of target genes was evaluated by RT‒qPCR. PEI nanoparticles increased target gene silencing compared to naked dsRNAs (up to 80%), whereas CS-TPP-dsRNA nanoparticles decreased gene silencing (0-20%) or led to the same level of gene silencing as the naked dsRNAs (up to 50%). We next evaluated the effects of targeting a single gene or simultaneously targeting two genes via the injection naked dsRNAs or dsRNAs complexed with PEI (500 ng) on CBW survival and phenotypes. Overall, gene expression analysis demonstrated that the treatments with PEI targeting either a single gene or multiple genes induced greater gene silencing compared to naked dsRNA (~60%). In addition, injection of dsJHEH/JHDK, severely affected CBW survival (18% for PEI nanoparticles and 47% for naked dsRNA) and metamorphosis. Phenotypic alterations such as uncompleted pupation or malformed pupae suggest that JHEH and JHDK are involved in developmental regulation. Moreover, CBW fed with dsJHEH/JHDK+PEI (1000 ng/g) showed significantly lower survival (55%) than CBW fed the same combination of naked dsRNAs (30%). Our findings demonstrated that PEI nanoparticles could be used as an effective tool for evaluating the biological role of target genes in CBW since they increase the RNAi response.